Strengthening Civic Unity Through Effectiveness of The Four Pillars Socialization Program in Indonesia - Siki Andri Putra; Izzatusholekha Izzatusholekha; Andriansyah Andriansyah; Taufiqurokhman Taufiqurokhman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The persistent challenges of social fragmentation in Indonesia, particularly those rooted in ethnicity, religion, race, and inter-group (SARA) issues, highlight the urgency of reinforcing national values. To address this, the People’s Consultative Assembly of the Republic of Indonesia (MPR RI) initiated the Four Pillars Socialization Program, encompassing Pancasila, the 1945 Constitution, the Unitary State of the Republic of Indonesia, and Unity in Diversity. This study aims to evaluate the effectiveness of the program in strengthening civic unity and minimizing divisive sentiments. A qualitative approach with a descriptive-analytical design was employed, involving purposively selected participants consisting of community members, local leaders, and program facilitators. Data were collected through semi-structured interviews, program documents, and observations, while thematic analysis guided interpretation. The research applied the effectiveness framework of Kettner, Moroney, and Martin, which includes five indicators: Effort, Cost Efficiency, Results, Cost Effectiveness, and Impact. The findings reveal that while program efforts and coverage are extensive, cost efficiency and long-term impact remain inconsistent due to uneven resource allocation and the absence of systematic follow-up. Nevertheless, participants reported enhanced awareness of national values and greater civic enthusiasm. The study concludes that although the Four Pillars Socialization Program has strengthened short-term civic unity, its long-term sustainability requires continuous evaluation, cost adjustments, and integration with educational and cultural initiatives. These insights provide strategic implications for policymakers to refine civic education and counter SARA-related conflicts.